2022
DOI: 10.3390/nu14040844
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Pattern Associated with the Risk of Hyperuricemia in Chinese Elderly: Result from China Nutrition and Health Surveillance 2015–2017

Abstract: Our current study aimed to estimate the relationship between dietary patterns and hyperuricemia among the Chinese elderly over 60 years old. All the data were obtained from China Nutrition and Health Surveillance during 2015–2017. A total of 18,691 participants who completed the whole survey were included in our statistical analysis. The definition of hyperuricemia was 420 μmmol/L (7 mg/dL) for male and 360 μmmol/L (6 mg/dL) for female. Exploratory factor analysis was applied to explore posterior dietary patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 32 publications
0
27
0
1
Order By: Relevance
“…The current study showed that the HUA prevalence in the insufficient physical active population was significantly higher than in the sufficient physical active population. However, in Yang’s [ 30 ] and Wang’s [ 37 ] study, the differences between the insufficient physical active population and sufficient physical active population were not observed. With regard to diet intakes, no positive results of the HUA prevalence were observed in bean and nut intake, fruit intake and milk intake analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study showed that the HUA prevalence in the insufficient physical active population was significantly higher than in the sufficient physical active population. However, in Yang’s [ 30 ] and Wang’s [ 37 ] study, the differences between the insufficient physical active population and sufficient physical active population were not observed. With regard to diet intakes, no positive results of the HUA prevalence were observed in bean and nut intake, fruit intake and milk intake analyses.…”
Section: Discussionmentioning
confidence: 99%
“…All the potential covariates were considered in this study to observe the influent power of dietary factor to HUA. (1) Genders; (2) Residence locations were categorized into urban and rural by region codes (100- for urban and 200- for rural) prescribed by the National Bureau of Statistics; (3) Geographic regions (east, central and west) were defined by National Bureau of Statistics, where east areas included Beijing, Tianjin, Hebei, Liaoning, Shanghai, Jiangsu, Zhejiang, Fujian, Shandong, Guangdong, Hainan, Central areas included Shanxi, Jilin, Heilongjiang, Anhui, Jiangxi, Henan, Hubei, Hunan, and West areas included Inner Mongolia, Guangxi, Chongqing, Sichuan, Guizhou, Yunnan, Tibet, Shaanxi, Gansu, Qinghai, Ningxia, and Xinjiang; (4) Participants were divided into four age groups: 18–29 years, 30–39 years, 40–49 years and 50–64 years; (5) Education level was categorized as low (primary school or below), moderate (junior school) and high (high school or above); (6) According to the annual income of household, four groups were established by conception of middle-level income persons and classification standard in China: low (<65,141.7 CNY), moderate (65,141.7–193,494.9 CNY), high (>193,494.9 CNY) and unknown/unclear; (7) Body mass index (BMI) was categorized as underweight (BMI < 18.5), normal (18.5 ≤ BMI < 24.0), overweight (24.0 ≤ BMI < 28.0), and obese (BMI ≥ 28.0) [ 26 ]; (8) Smoking was classed as never smoked, formerly smoked or currently smoke; (9) Physical activity status was decided based on weekly total metabolic equivalent (MET) and total weekly duration of different exercise levels: insufficient (MET < 600), sufficient (600 ≥ MET) [ 27 ]; (10) Diabetes mellitus was diagnosed according to the ADA 2010 criteria (FPG level ≥ 7.0 mmol/L and/or HbA1c concentration ≥ 6.5%) [ 28 ]; (11) According to the guidelines of Chinese adult dyslipidemia prevention and treatment (2016 revised edition), those with total cholesterol ≥ 6.2 mmol/L or triglyceride ≥ 2.26 mmol/L or LDL ≥ 4.14 mmol/L or HDL < 1.04 mmol/L were considered as dyslipidemia [ 29 ]; (12) Hypertensive was identified in those whose mean systolic blood pressure was ≥ 140 mmHg and/or mean diastolic blood pressure ≥ 90 mmHg and/or received antihypertensive medicine within two weeks [ 30 ]; (13) Vegetarian was the consumer of plant-based diet with no dairy products and eggs intake.…”
Section: Methodsmentioning
confidence: 99%
“…Dietary information was assessed by a widely used semi-quantitative FFQ to assess habitual food intake from the preceding year [ 23 ]. This FFQ, composed of 64 food items, was designed to investigate the dietary intake of Chinese residents.…”
Section: Methodsmentioning
confidence: 99%
“…Diet may partly mediate the simultaneous elevation of TG and SUA. 65 In addition, TG synthesis requires NADPH as the reducing molecule of the fatty acid synthase complex, which is mainly produced in the pentose phosphate metabolic pathway. Hypertriglyceridemia may be accompanied by an upregulated pentose phosphate pathway and therefore a concomitant increase in SUA synthesis.…”
Section: Discussionmentioning
confidence: 99%